PENGGUNAAN INSEKTISIDA RUMAH TANGGA TERHADAP RESISTENSI NYAMUK AEDES sp DI GAMPONG LAMPASEH ACEH TAHUN 2025 - Nurfida, Nurfida; Sofia, Sofia; Nasrulla, Nasrulla; Junaidi, Junaidi (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2025)
The improper use of household insecticides can reduce vector susceptibility and potentially lead to the emergence of resistant mosquito populations. In Lampaseh Village, most residents routinely spray insecticides indoors as an effort to prevent mosquito nuisance. However, despite regular spraying, residents continue to report the presence of mosquitoes. The number of Dengue Hemorrhagic Fever (DHF) cases in this area is relatively low, yet cases are reported every year. This indicates that the threat of Aedes mosquitoes as vectors of the dengue virus has not been completely eliminated and that control efforts still require serious attention. This study is descriptive in nature, aiming to illustrate household insecticide use patterns and identify the resistance status of Aedes sp. mosquitoes through laboratory-based Susceptibility Tests. Data on insecticide use were collected through interviews with 86 households, while resistance testing was conducted on 75 adult mosquitoes. Findings are presented in narrative and percentage form. The results showed that the application of household insecticides was not fully in line with recommended practices. The majority of respondents reported using aerosol sprays (40%), which pose a risk of excessive application. Most spraying was conducted at night (81.40%), whereas the peak biting activity of Aedes aegypti occurs in the morning and late afternoon. In terms of frequency, the majority (58.14%) did not spray daily. Nevertheless, the Susceptibility Test demonstrated that mosquitoes remained susceptible to cypermethrin, with a mortality rate of 100%. In conclusion, the reduced effectiveness of insecticides in the field is not caused by mosquito resistance but is more likely influenced by suboptimal application practices. Simple preventive measures such as maintaining environmental sanitation, draining water containers, and eliminating stagnant water remain more effective strategies to disrupt the mosquito life cycle.